Pathomorphological changes of aorta in fetuses and newborns exposed to experimental maternal escherichiosis - Markovskyi, Vladimir; Zvereva, Irina (Journal of Education, Health and Sport, 2018)
Intrauterine infections occupy a leading place in the perinatal mortality structure. The aim of this study was to identify the morphological features of the aorta in progenies born from mothers with subacute prolonged infectious and inflammatory process. Two experimental studies were performed on WAG line laboratory rats. The comparison group consisted of newborns died due to acute postnatal hypoxia. The main group included fetuses and newborns born from Escherichia coli infected mothers. The differences between the vessels of two study groups were not observed in macroscopic examination. In the group of progenies born from infected mothers, the average thickness of the aorta increased in comparison with the group under hypoxia influence, due to the inner and middle membranes, which can be interpreted as the sclerotic changes development. There was tunica adventitia volume increase in the group with hypoxia, which can be explained by edema caused by increased vascular permeability. Morphological signs of endothelial dysfunction were found in both study groups, which were expressed in the endotheliocytes flattening with their subsequent desquamation more pronounced in the group with hypoxia. It is apparently related to the process severity. There is a violation of the elastic and collagen fibers ratio towards the second in the vessel wall under the hypoxia influence, which reduces the elastic properties of the aorta.